Modeling femtosecond pulse propagation and high harmonics generation in hollow core fibers - Tosa Valer (EDP Sciences, 2021)
One way to increase the well known low efficiency of high order harmonics generation is to place the gas medium in a hollow core waveguide. The numerical model used to obtain driving and harmonics field configuration along and across the waveguide was developed for an arbitrary gas density profile and arbitrary fiber diameter modulation. The model was tested against experimental measurements and excellent agreement was obtained for the fluorescence emission along the waveguide. We analyse the influence of the diameter modulation which result from the fabrication process on both pulse propagation and on harmonic generation.